Solar powered internet of things for urban framing - Wang, Jiaxin (2019)
For Food Security, one of the key aims is to have the scarce land resource like Singapore to provide the food resource close to the community. Recently, there is necessity for innovative techniques for monitoring the condition of plants soil, lighting or food sources that are grown in the urban landscape like Singapore. In this project, the development and design of novel sensing and monitoring techniques for the urban farming environment will be involved. Firstly, various kinds of IoT platforms and IoT elements will be introduced. In addition, the working principles of radio frequency and Bluetooth low energy commutation will be illustrated. Also, with the help of IDE programming, the data transmission between all the things become easier, which perfectly matches the concept of internet of things. The report will introduce small basic IDE programming projects and how to combine different kinds of sensors with Arduino design. Finally, the project requires to design a system with functions like temperature measurement and TDS value detection inside water. A project demonstration of the system designed and an oral presentation will conclude the project.